1973
DOI: 10.1254/jjp.23.57
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Production of Stress Erosion in the Mouse Stomach and Related Pharmacological Studies

Abstract: Abstract-A stress method in mice which develops gastric erosions was devised. This stress procedure consisted of restraint and water immersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The restraint cages were prepared according to the literature (17). Usually, mice were restrained for 2 con secutive days.…”
Section: Tamatsukurimentioning
confidence: 99%
“…The restraint cages were prepared according to the literature (17). Usually, mice were restrained for 2 con secutive days.…”
Section: Tamatsukurimentioning
confidence: 99%
“…Restraint and water immersion stress produces a high incidence and severity of gastric lesions in rats (1, 2) and mice (3,4). Exposure of rats to this stress induced an increase in gastric motility (5), and thus the increased gastric motility as well as the presence of gastric juice (6) and the disorder of gastric mucosal blood flow (7,8) was postulated to play an im portant role in forming stress-induced gastric lesions (9,10).…”
mentioning
confidence: 99%
“…These and subsequent studies have suggested that enhanced gastric secretion (7) and/or motility (8,9) are important in the etiology of stress ulcer, giving a theoretical basis for the development of antiulcer drugs that suppress gastric secretion.…”
mentioning
confidence: 99%